Knowledge, Attitude, and Practice Regarding Diabetes Mellitus among General Public and Diabetic Patients in Riyadh, Saudi Arabia - Asdaq, Dr. Syed Mohammed Basheeruddin (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Awareness among patients and general population is a major determinant for prevention of diabetes and its complications. The elucidation of status of knowledge and attitude as well as prevalent practices are the principle indicators of awareness in various populations. Aim: Theaim of this study was to explore knowledge, attitude and practice (KAP) regarding diabetes mellitus (DM) among nondiabetic (nonDM) population and diabetes mellitus (DM) patients in Riyadh, Saudi Arabia. Methods: A cross-sectional study was conducted among adults (784, aged 18 years and above, 47% male and 53% female) participants selected purposively from the outpatient department of two hospitals of Riyadh. After obtaining consent from participants, KAP were assessed by a validated, pre-structured, interviewer-administered questionnaire (Arabic translated). The results were evaluated as average scores as well as levels in KAP. Univariate and bivariate statistical analysis were done as appropriate. Multivariate linear regression was done to examine the association between diabetes related KAP and other covariates. Results: Overall, highpercentage of participants exhibited good knowledge, attitude and practice score, 75% , 46% and 43%, respectively. Among DM participants, knowledge level was good in 32%, while 56% and 55% of them showed positive attitude and practice, whereas, in the nonDM group, only 25% demonstrated good knowledge and 48% & 52% respectively, showed positive attitude and practice. The KAP towards diabetes was found to be better among people who were living with diabetes compared to people without diabetes. DM males scored better both in knowledge and attitude, compared to their female counterparts (p< 0.001). However, females showed better practice compared to males. The level of education positively correlated with KAP scores (p < 0.001). On linear regression analysis, knowledge scores correlated strongly with marital status, location, diabetic state, and attitude. On the other hand, the attitude score was found to be associated with sex, DM status and knowledge. Finally, practice score was found to be associated with educational level, location, DM status, knowledge and attitude. Conclusions: Even though the majority (75%) of the participants have knowledge on diabetes, but their level of knowledge is not high (overall only 29% have good knowledge), also attitude and practice is not very encouraging. It appears that the current status of knowledge on diabetes did not translate into positive attitude and practices. Therefore, more emphasis should be given to address the issue of negative attitude and practices towards diabetes mellitus among general public as well as DM patients in Riyadh through community educational programs.